2009
DOI: 10.1007/s00330-009-1597-x
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial invasion in endometrial cancer: diagnostic performance of diffusion-weighted MR imaging at 1.5-T

Abstract: DW imaging proved to be accurate in assessing myometrial invasion, and it could replace dynamic imaging as an adjunct to routine T2-weighted imaging for preoperative evaluation of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 38 publications
4
62
1
Order By: Relevance
“…MRI DWI provides roughly the same level of diagnostic ability as contrast MRI, and in many cases, it further enables the evaluation of tumor spread. However, according to the studies of Rechichi et al 25 , DWI was more effective when a comparison was implemented using 1.5 TMRI between DWI and contrast MRI. In this study, endometrial cancer demonstrated higher signal intensity on DWI than normal endometrium, and the addition of diffusion-weighted imaging to the T2-enhanced axial view further improved the rate of accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…MRI DWI provides roughly the same level of diagnostic ability as contrast MRI, and in many cases, it further enables the evaluation of tumor spread. However, according to the studies of Rechichi et al 25 , DWI was more effective when a comparison was implemented using 1.5 TMRI between DWI and contrast MRI. In this study, endometrial cancer demonstrated higher signal intensity on DWI than normal endometrium, and the addition of diffusion-weighted imaging to the T2-enhanced axial view further improved the rate of accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of DWI to routine imaging may improve staging accuracy, not only with respect to myometrial invasion where accuracies of 62-90% have been reported, but for highlighting the tumormyometrial interface in cases where the tumor is isointense to myometrium on T2-W images and/or shows marked peritumoral enhancement on post contrast imaging [13,[18][19][20] In contradistinction to endometrial cancer, the use of intravenous contrast in not routine, rather it is reserved for the following situations: small lesions that are not well depicted on T2-W images (especially if patient is being considered for trachelectomy); post treatment surveillance; and aiding tumor origin in patients with adenocarcinoma involving the lower uterine segment and the cervix. The following table adapted from reference [3] summarizes the revised FIGO staging of cervical cancer with MRI correlates:…”
Section: Methodsmentioning
confidence: 99%
“…Background: Most institutions and educational texts instruct that fasting for at least 6 hours if not more is needed to perform an ultrasound scan of the abdomen to get the best quality images and make an accurate diagnosis of the clinical question being asked. 18,19,20,21 Imaging quality is affected by bowel gas and content which may obscure underlying organs. 4,5 Fasting expands the gallbladder, which when contracted can interfere with diagnosing pathology that may be present.…”
Section: Usamentioning
confidence: 99%
“…Although lower ADC values in high-grade tumors have been reported, some studies have reported no correlation between ADC values and histological grades (115,116). DWI is accurate for differentiating stage IB from stage IC and can be used as an adjunct for routine T2W MRI during pre-operative evaluation of endometrial cancer (111,117).…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%